2022
DOI: 10.1007/s11357-022-00514-6
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip strength and risk of cognitive outcomes: new prospective study and meta-analysis of 16 observational cohort studies

Abstract: Handgrip strength (HGS), a measure of muscular strength, might be a risk indicator for cognitive functioning, but the evidence is not consistent. Using a new prospective study and meta-analysis of published observational cohort studies, we aimed to evaluate the prospective associations of HGS with poor cognitive outcomes including cognitive impairment, dementia and Alzheimer’s disease (AD). Handgrip strength, measured using a Martin-Balloon-Vigorimeter, was assessed at baseline in a population-based sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 87 publications
3
19
0
Order By: Relevance
“…The reported link between grip strength and cognition aligns with previous studies [13,15,45], which suggests that grip strength may serve as a complementary measure of cognitive ability in aging adults. Going beyond limited domains or insensitive cognitive measures, we investigated a broader constellation of cognitive metrics spanning domains of memory, executive function, reasoning, and processing speed that are sensitive to subtle, early changes related to aging.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The reported link between grip strength and cognition aligns with previous studies [13,15,45], which suggests that grip strength may serve as a complementary measure of cognitive ability in aging adults. Going beyond limited domains or insensitive cognitive measures, we investigated a broader constellation of cognitive metrics spanning domains of memory, executive function, reasoning, and processing speed that are sensitive to subtle, early changes related to aging.…”
Section: Discussionsupporting
confidence: 86%
“…A recent community-based study also found that older adults in the lowest quantile of muscular strength have a higher likelihood of suffering from depressive symptoms and suicidal ideation [12]. Moreover, meta-analytic findings have consistently implicated the predictive value of grip strength for health outcomes, highlighting its crucial role as a clinically useful indicator for monitoring cognitive impairment and progression of neurodegenerative diseases [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies indicate that in older adults, low grip strength is associated with subsequent manifestations of cognitive dysfunction, diagnoses of mild cognitive impairment (MCI), and the incidence of various types of dementia. [1][2][3][4] It is also apparent that rates of decline in grip strength and cognitive function are closely aligned. 5 Although grip strength is often treated as a proxy for "muscular fitness" (for example, 6 ) there are no indications that cognitive and muscle function are linked.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is one of the common aspects among people who are socio-economically vulnerable, alongside poverty, low education, and unemployment, and older people are a category that deserves much attention in national prevention strategies [ 2 ]. As such, interest in the health of older people is increasing, and in particular, many related studies on muscle strength have been conducted [ 3 , 4 , 5 , 6 , 7 , 8 ]. Muscle strength is an important factor for maintaining vitality, mobility, and physical function in old age [ 3 ], and muscle strength loss is an independent risk factor for high mortality in older people [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the 2019 Asian Working Group recommended using handgrip strength as an indicator of muscle strength to diagnose sarcopenia [ 11 ]. It has been reported that handgrip strength is associated with future fracture risk [ 13 ] and may be a risk indicator for poor cognitive outcomes [ 7 ]. In addition, it was shown that handgrip strength was considerably associated with quality of life after hip fracture surgery in the elderly [ 14 ].…”
Section: Introductionmentioning
confidence: 99%